Electrical Engineering Practicum: The Place of Virtual Laboratory in Nigerian Universities - Isaac John Ibanga; Gideon Fwah Karnilius; Tanimu Anjili; Raphaelline Hyelaiti (The Indonesian Institute of Science and Technology Research, 2023)
This study examined the level of awareness, perception, and utilization of virtual laboratories in Nigerian Universities by Electrical Engineering lecturers. The study was guided by three specific objectives and three survey research types. One hundred twenty-one lecturers in electrical engineering from 8 universities in Nigeria's Northeast comprised the study's population. Because the total population size was manageable, the study used whole-population sampling. Data was collected using a validated questionnaire. A reliability index of 0.79 was determined using Cronbach Alpha. Mean, and standard deviation were used to answer the research questions. The findings revealed that all the electrical engineering lecturers in Nigerian Universities are highly aware of Virtual Laboratories, and all the electrical engineering lecturers in Nigerian Universities rarely utilized Virtual Laboratories. The study recommended that the National University Commission should use all of its resources to promote the development of electrical engineering practicum by providing virtual laboratories to all universities in Nigeria, as the study found that electrical engineering lecturers in Nigerian universities have a high level of awareness of virtual laboratories; in addition to supporting physical laboratories in the universities, the administration should provide for the training of laboratory technicians and electrical engineering lecturers in Nigerian universities on how to effectively use the virtual laboratory facilities for conducting various types of experiments.